2004
DOI: 10.1128/mcb.24.7.2614-2626.2004
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cδ Selectively Regulates Protein Kinase D-Dependent Activation of NF-κB in Oxidative Stress Signaling

Abstract: Protein kinase D (PKD) participates in activation of the transcription factor NF-B (nuclear factor B) in cells exposed to oxidative stress, leading to increased cellular survival. We previously demonstrated that phosphorylation of PKD at Tyr463 in the PH (pleckstrin homology) domain is mediated by the Src-Abl pathway and that it is necessary for PKD activation and subsequent NF-B induction. Here we show that activation of PKD in response to oxidative stress requires two sequential signaling events, i.e., phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
245
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(253 citation statements)
references
References 58 publications
5
245
0
3
Order By: Relevance
“…Multiple lines of evidence suggest PKD as a sensor of oxidative stress involved in several signaling pathways. [15][16][17] Therefore, we asked whether the interaction of PKD with DAPk might be regulated by oxidative stress. To induce oxidative stress, cells were treated with hydrogen peroxide (H 2 O 2 ) for 2min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple lines of evidence suggest PKD as a sensor of oxidative stress involved in several signaling pathways. [15][16][17] Therefore, we asked whether the interaction of PKD with DAPk might be regulated by oxidative stress. To induce oxidative stress, cells were treated with hydrogen peroxide (H 2 O 2 ) for 2min.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorylation of tyrosine 463 in PKD by Src, in concert with phosphorylation of the PKD activation loop by PKC-d, were shown to induce the activation of NF-kB by PKD leading to increased cellular survival. 16,17 More recently, Zhang et al, 15 demonstrated a PKC-independent activation mode of PKD under oxidative stress, which stimulates JNK phosphorylation via the activation of ASK1, consequently leading to cell death. However, how PKD is regulated in the latter cellular setting was not described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After ruling out a number of putative Src substrates to interfere with IB degradation [28][29][30][31][32][33][34] Ser/Thr phosphatase PP2A was found to be the critical component. PP2A is known to modulate NFB activity [47].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that in response to mROS PKD1 can be activated via Src-mediated phosphorylation events. [23][24][25] Src is a redox-regulated kinase and its activation involves the oxidation of cysteine residues which then results in intramolecular disulfide bond formation and increased kinase activity. 26 This can be further potentiated by ROS-mediated oxidation and inactivation of regulatory phosphotyrosine phosphatases.…”
mentioning
confidence: 99%